Сидоровское городище - Кравченко, Э.Е.; Давыденко, В.В. (Степи Европы в эпоху средневековья, 2001)
The investigation of a big archaeological complex consisting of a hillfort, a big settlement (the total area of 100 hectare) and burials, situated not far from the village of Sidorovo (Slavyansk district of Donetsk region) were resumed in 2000. Before this only occasional excavations were carried out by the Kharkov State University expedition in 1972. In 1994, 1996-1997 the Donetsk Museum of local lore expedition investigated a Moslem semetry (No 1) not far from the settlement. The cemetery was believed to date back to the second half of the IXth - the Xth c.c. Such early dating of the Moslem burial caused strong objections and a research of the settlement has been resumed. In 2000 the excavations were carried out at a greater territory (more than 1000 sq. m). 4 dwellings, 2 pottery furnaces, 27 household pits and 12 burials were cleared out. The burials belonged to a Moslem cemetery (No 2) adjacent to the dwellings. Stratigraphy of the cemetery suggests simultaneous existence of the complex constituents: the dwellings, household pits and burials. The stock material gives evidence that the cleared out objects date back to the second half of the IXth-the Xth cc. In general, the materials obtained and the data that have been published earlier give evidence that the Sidorovo hillfort emerged in the second half of the Vlllth c. and survived up to the end of the Xth c.The life of the hillfort was closely connected wilh a busy trade route passing near it. The hillfort prospered in the second half of the IXth - the Xth c.c. At those times a big Moslem community lived there, it is considered to be one of the earliest Moslem communities in Eastern Europe.